Influencia de las variables tiempo y distancia en la eficacia del juego con transformaciones en cuatro equipos de balonmano de alto nivel. Posibilidades para la aplicación en el entrenamiento - Garcia, J. A.; Aniz Legarra, I.; Arellano, J. I.; Dominguez, J. O.; Garcia, T. (European Journal of Human Movement, 2004)
The objective of this study is to determine the transcendency that they have in the handball game the transformations of the attack system and the consequences that can be extracted for the training. For it has been used it as sample to the first four teams of the league ASOBAL in the season 2001-2002, being analyzed all the confrontations among these four teams (24 games). The results show that the game with transformation of the system of attack initial reaches to 24,06% of the time of attack in specific positions. The P. San Antonio achieved a bigger effectiveness in the game with transformations that in the game without transformations (p = ,003). In the same way it was identified that the P. San Antonio is more effective in the game with transformations that the F.C. Barcelona (p = ,046) as for the profile of the attack game with and without transformations more reduced times they were identified in the attainment of the effectiveness playing by means of transformations (between 3 and 6 seconds) that without them. Regarding the distance they met significant differences equally for the game with transformation in their comparison with the game without transformation from the distance of more than 9 m. (p = ,0003).